DESIGN AND APPLICATION OF SAVINGS AND LOANS IN COOPERATION JALA BHAKTI SEDANA BASED WEB - I Gusti Ngurah Gandhi Prabawa; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Jala Bhakti Sedana is a cooperative located in Jala Sidhi Amerta Temple in Sidoarjo. It provides savings and loan for all Hindu people who become its member. So far, all the transaction data is recorded in manual way (using book) therefore the officer has difficulty in finding data member and the transaction data is at risk of being lost. Moreover, the calculation of surplus distribution is done by non-monetary background person so that it cannot be done fast. This causes that the surplus of cooperative cannot be distributed on time. The solution offered by the writer is the making of web-based application for savings and loan activity in cooperative of Jala Bhakti Sedana which is able to record all the savings and loan transaction and doing surplus calculation. This application has several main processes such as savings and loan data recording, calculation of operating profit, calculation of surplus allocation, calculation of savings surplus, and calculation of loan surplus. After being tested, this application is able to help the officer to note savings and loan transaction in cooperative. Beside, it also helps treasury officer making cooperative surplus counting so that it can be distributed to all member on time annually